Biogenesis of RNA Polymerases in Yeast - Garrido-Godino, Ana I.; Gutiérrez-Santiago, Francisco; Navarro, Francisco (Frontiers in Molecular Biosciences, 2021)
Eukaryotic RNA polymerases transcriptional processes have been extensively investigated and structural analysis of eukaryotic RNA pols has been explored. However, the global assembly and biogenesis of these heteromultimeric complexes have been poorly studied. Despite nuclear transcription being carried out by three RNA polymerases in eukaryotes (five in plants) with specificity in the synthesis of different RNA types, the biogenesis process was proposed to be similar, at least for RNA pol II, to bacteria, which contains only one RNA pol. The formation of three different interacting subassembly complexes to conform the complete enzyme in the cytoplasm, prior its nuclear import, has been assumed. In Saccharomyces cerevisiae, recent studies have examined in-depth the biogenesis of RNA polymerases by characterising some elements involved in the assembly of these multisubunit complexes, some of which are conserved in humans. This work reviewed the latest studies governing the mechanisms and proteins described as being involved in RNA polymerases biogenesis in yeast